Association between postnatal maternal nutritional status, maternal HIV disease progression and infant feeding practices in 4 clinics in Pretoria, South Africa - MacIntyre, Una Elizabeth (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.